2003
DOI: 10.1038/sj.ijir.3901010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of erectile dysfunction and associated factors among men without concomitant diseases: a population study

Abstract: We interviewed a population sample of 2412 men aged 40-70 y in Brazil, Italy, Japan and Malaysia about medical history, lifestyle habits and sexual behavior. Men were classified as having moderate or complete erectile dysfunction (ED) if they reported to be sometimes or never able to achieve and maintain an erection satisfactory for sexual intercourse, respectively. There were 1335 men with no diagnosis of cardiovascular or prostate diseases, diabetes, ulcer or depression, nor taking hormones. The prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 18 publications
9
68
2
4
Order By: Relevance
“…Increased risk of ED among current smokers who smoke ≥ 20 cigarettes per day compared to never smokers was reported by studies conducted in Australia [11] (adjusted OR = 1.39; 95% CI, 1.05, 183), China [12] (adjusted OR = 1.47; 95%CI, 1.00, 2.16), Canada [13] (adjusted OR for 25-50 pack-years was 2.11, 95%CI, 1.02, 4.36), Italy (adjusted OR for 10-20 yr of smoking was 1.6, 95%CI, 1.2, 2.0, with a similar OR for ≥ 20 years of smoking), [14] and a crossnational survey of Brazil, Italy, Japan, and Malaysia [10] (adjusted OR for ≥ 30 cigarettes/d was 2.3, 95%CI, 1.19, 4.49). Findings from the BACH study show a similar effect of cumulative pack-years among both former and current smokers with an adjusted OR of 1.70 (95%CI, 1.04, 2.77) for ≥ 20 pack-years of smoking.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Increased risk of ED among current smokers who smoke ≥ 20 cigarettes per day compared to never smokers was reported by studies conducted in Australia [11] (adjusted OR = 1.39; 95% CI, 1.05, 183), China [12] (adjusted OR = 1.47; 95%CI, 1.00, 2.16), Canada [13] (adjusted OR for 25-50 pack-years was 2.11, 95%CI, 1.02, 4.36), Italy (adjusted OR for 10-20 yr of smoking was 1.6, 95%CI, 1.2, 2.0, with a similar OR for ≥ 20 years of smoking), [14] and a crossnational survey of Brazil, Italy, Japan, and Malaysia [10] (adjusted OR for ≥ 30 cigarettes/d was 2.3, 95%CI, 1.19, 4.49). Findings from the BACH study show a similar effect of cumulative pack-years among both former and current smokers with an adjusted OR of 1.70 (95%CI, 1.04, 2.77) for ≥ 20 pack-years of smoking.…”
Section: Discussionmentioning
confidence: 87%
“…A number of modifiable risk factors are associated with ED, including obesity, hypertension, unfavorable lipid levels, alcohol abuse, physical activity, and cigarette smoking [5][6][7][8]. The association between ED and current smoking has been reported in previous cross-sectional studies [9][10][11][12][13][14]. Additionally, longitudinal data from the Massachusetts Male Aging Study (MMAS) and the Health Professionals Followup Study (HPFS) have reported increased incidence of ED among smokers [7,15].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The increased impact of relational factors in aging individuals could partly explain the observed age- Aging and pathogenesis of ED G Corona et al related, comorbidity-independent, increase in the prevalence of ED, which was previously described. 35 These findings might suggest that a sexuological-psychotherapeutic approach to ED should be more focused on the relational disturbances in aged patients, and on intrapsychic aspects in younger subjects. As expected, the organic component, as measured by SIEDY r , increases with age, and it accounts for a greater proportion of severity of ED in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Among a wide variety of available treatments for ED, the oral administration of phosphodiesterase-5 (PDE-5) inhibitors represents an attractive and widely used therapeutic option.…”
Section: Introductionmentioning
confidence: 99%